Profile of congenital malformations in a tertiary care level neonatal intensive care unit - Tirumani, Hima Bindu; Khatija, Shafia (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital malformations are important causes of infant and childhood deaths, chronic illness and disability. Methods: This prospective observational study was conducted over a period of one year in Princess Esra Hospital, a tertiary level neonatal intensive care unit, Deccan College of Medical Sciences, Hyderabad, Telangana, India. All new-borns admitted to the neonatal intensive care unit over a period of 1 year from June 2014 to June 2015 were included in the study. Results: The incidence of congenital malformations (CMF) in the present study is 3%. Among the major congenital malformations, the central nervous system (CNS) and gastrointestinal (GI) malformations were more frequent than others contributing to 28.9% each. The male neonates were more frequently involved than females. Association of low birth and prematurity with increased risk of congenital malformations is also documented. Conclusions: Early prenatal diagnosis and management of common anomalies is strongly recommended.